Prevalensi Kejadian Gangguan Menstruasi Berdasarkan Indeks Masa Tubuh (IMT) Pada Siswi Kelas VII Mts Hasyim Asy’ari Kedungmegarih, Kec. Kembangbahu, Lamongan - Asyaul Wasiah; Lilik Darwati (Jurnal Keperawatan Muhammadiyah, 2023)
Menstruation is a natural process experienced by women, this becomes a major problem in society if there is a menstrual disorder. Disorders that often occur include irregular menstrual cycles, menstrual volume disturbances, either prolonged or abnormal bleeding, pain disorders or dysmenorrhea, or premenstrual syndrome.Methods: This type of research is an analytical research design with a cross sectional approach. The research population was all female students of class VII  MTs Hasyim Asy’ari Kedungmegarih Kec. Kembangbahu Lamongan. The number of samples is 48 female students. Using the whole population method (total sampling), sampling is done with non-probability. The statistical test used in this study was Chi-Square. To test the significance, the significance limit was used, which was 5% (α = 0.05).Results:   After testing the hypothesis using the chi square method with a significance level of 0.05 (α = 5%), the p value (p value) is 0.002 (p < 0.05), then Ho is rejected, which means that there is a relationship between menstrual disorders and the mass index. The female student body of class VIII MTs Hasyim Asy’ari Kedungmegarih Kec. Kembangbahu Lamongan